Makna Mawar dan Melati dalam Sajak dan Lagu Sebuah Analisis Wacana tentang Metafora - Abu Katili, Adriansyah (Pascasarjana, Universitas Negeri Gorontalo, 2024)
This article contains a discourse analysis of the meaning of roses and jasmine in songs and poems. The poem analyzed is